A Manifesto for exercise science – a vision for improving the health of the public and planet. Issue 10 (19th May 2022) - Smith, Andy; Broom, David; Murphy, Marie; Biddle, Stuart
ABSTRACT: In this manifesto, we make the case that Exercise Science can and must do more to improve the health of the public and the planet. Post pandemic, our vision for Exercise Science is one of a maturing scientific discipline reaching outwards from a base of strong empirical evidence to have a profound and sustained positive global impact on health. In each of the three main areas of the discipline – research, teaching, and professional practice – a new and distinctive approach is needed. We propose 12 points of action, in no particular order, for a). quality, rigour, and professional standing, and b). reach, relevance, and public engagement and make numerous suggestions for action and change. We encourage the teachers, researchers and practitioners of Exercise Science to consider and act on these recommendations. We hope that this manifesto can help create a shared sense of purpose amongst the global Exercise Science community and further the principles of equality, diversity and inclusion. To act on these principles, we need to cultivate a discipline that encourages more women, people who experience racism and other forms of discrimination, and people with a disability to become involved in the discipline.